Gestión administrativa y contable de la inversión inmovilizada - Cagua Castillo, Cinthya Lorena (2025)
The main objective of this degree work called “Administrative and accounting management of immobilized investment” is to analyze the internal control of the fixed asset inventory in the operating expenses of the Charity Society. For which a methodology with a quantitative and qualitative approach was used that allowed the collection of information for the respective analysis and interpretation of the results; Exploratory research was also used to facilitate the identification of possible variables. It should be noted that the theoretical and empirical methods provided a complete view of the problem. An interview was applied, using a questionnaire directed at the actors involved. The results of the research reveal that there is a relationship between the administrative and accounting management of the immobilized investment with the reduction of operating expenses. In this same context, it is concluded that the implementation of a proposal for an administrative and accounting management system will not only contribute to financial efficiency, but also to the improvement of the educational quality of the Charitable Societ.